PENGANGGARAN DANA BANTUAN OPERASIONAL SEKOLAH (PERSPEKTIF NEW INSTITUTIONAL SOCIOLOGY) - SRI RAHAYU ; Prof. Dr. Unti Ludigdo, SE, M.Si, Ak.Gugus Irianto,SE,MSA, Ph. D, Ak.Nurkholis, SE, M.Bus., Ph.D, Ak
This research aimed to comprehend the processes of fund budgeting of School Operational _x000D_ Assistance and its institutionalization. It employed ethnomethodology to deeply understand the daily_x000D_ practices of actors. The institutionalization process was exposed and comprehended through the_x000D_ perspective of new institutional sociology. The research found out that there are three patterns_x000D_ practiced by actors in the fund budgeting of School Operational Assistance in a research site, they are:_x000D_ 1) the single domination of a school’s principal, 2) the domination of a special group in a school, and 3)_x000D_ the school’s domination. The single domination means that the principal implements the fund_x000D_ budgeting of School Operational Assistance by his/her own. The domination of a special group means_x000D_ that the principal has invited some others in the school to get involved. The school’s domination means_x000D_ that all school internal elements get actively involved in the budgeting even though parents and_x000D_ external sides are closely jointed in the budget arrangement process only. Besides the principal, the_x000D_ school’s operator also plays as the main actor. The institutionalization process of the fund budgeting_x000D_ of School Operational Assistance consists of innovation, diffusion, legitimacy, and_x000D_ deinstitutionalization. The isomorphism indicators found are coercive, normative, and mimetic. _x000D_ Decoupling behavior appears to be the school response answering the change of the budgeting_x000D_ institution. The school implements compromise and avoid strategy. The actors interpret the School_x000D_ Operational Assistance is a formally administrative ceremony merely for a stability and a legitimacy of_x000D_ individual and organizational interests. Re-institutionalization of the basic of the fund budgeting of_x000D_ School Operational Assistance should be run by applying humane values and harmonious with the_x000D_ Indonesian’s philosophy of culture that is mutual cooperation. The researcher recommends that a_x000D_ mutual-cooperation based management can be a new basic of the fund budgeting of School_x000D_ Operational Assistance. _x000D_ Keywords: Isomorphism, Coercive, Normative, Mimetic, Decoupling, Deinstitutionalization, Reinstitutionalization